2016
DOI: 10.1002/2016gl070084
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the macroscopic state of electrons and the properties of chorus waves observed by the Van Allen Probes

Abstract: Plasma kinetic theory predicts that a sufficiently anisotropic electron distribution will excite whistler mode waves, which in turn relax the electron distribution in such a way as to create an upper bound on the relaxed electron anisotropy. Here using whistler mode chorus wave and plasma measurements by Van Allen Probes, we confirm that the electron distributions are well constrained by this instability to a marginally stable state in the whistler mode chorus waves generation region. Lower band chorus waves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 30 publications
9
58
0
Order By: Relevance
“…This corresponds to the location of a population of >50-mV/m waves identified in Tyler et al (2019), which were associated with plasmasphere erosion during active times. However, both upper-and lower-band chorus have been observed to have oblique populations Yue et al, 2016). The location of these very large-amplitude oblique waves is similar to that of quasi-oblique lower-band chorus observed by Li et al (2016) using time-averaged EMFISIS data.…”
Section: Discussionsupporting
confidence: 67%
“…This corresponds to the location of a population of >50-mV/m waves identified in Tyler et al (2019), which were associated with plasmasphere erosion during active times. However, both upper-and lower-band chorus have been observed to have oblique populations Yue et al, 2016). The location of these very large-amplitude oblique waves is similar to that of quasi-oblique lower-band chorus observed by Li et al (2016) using time-averaged EMFISIS data.…”
Section: Discussionsupporting
confidence: 67%
“…Spasojevic (2014) also showed a storm intensity dependence on chorus amplitude and occurrence, as larger storms had more, stronger, and longer lasting chorus activity than moderate storms. MacDonald et al (2008MacDonald et al ( , 2010 and Yue et al (2016) have previously shown that when an electron distribution correlated with chorus wave activity is observed, it typically has already relaxed to a more stable state. This was attributed to the changing geomagnetic field configuration with the increased geomagnetic activity of the main phase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies based on linear theory [Gary and Wang, 1996], PIC simulation , or observation [Gary et al, 2005;Yue et al, 2016] have suggested that the saturation A-‖ relation for whistler mode waves should satisfy equation (1). As discussed in section 1, linear theory cannot determine the value of S or in equation (1), because the distribution is assumed to be the unperturbed initial distribution all the time.…”
Section: The A-‖ Relationshipmentioning
confidence: 99%
“…However, in linear analysis, an assumption about the maximum linear growth rate ( m ) is needed to obtain values for S and . Recently, Yue et al [2016] used Van Allen Probes data and demonstrated that the electron temperature anisotropy constraint associated with excitation of whistler mode chorus waves is well described by equation (1). Here Ω is the unsigned electron cyclotron frequency.…”
Section: Introductionmentioning
confidence: 99%